The Familiarization of Post-Partum Blues Syndrome to Pregnant Women Through Health Promotion - Ulfa, Maria; Monica, Laily Prima; Wibisono, Wahyu (STIKes Patria Husada Blitar, 2022)
The most difficult period for women is going through a transition period in the post partum phase, such as changes in physically, psychologically, emotionally and socially. The existence of anxiety, panic attacks, fatigue, feelings guilty, the inability to take care of the baby and the absence of support from partners and family are the main factors causing the post partum blues. The purpose of this community service was to increase the knowledge of pregnant women about the post partum blues syndrome, the impact of post partum blues, introduction, and prevention as early as possible post partum blues. The method was n the form of counseling and providing education to a class of pregnant women in Jatinom village, Kanigoro, Blitar district. The result showed knowledge of pregnant women in the introduction of post partum blues syndrome were 5 participants (25%) in the good category, 5 participants (25%) in the sufficient category, 10 participants (50%) in the poor category. After the counseling, there was an increase in knowledge of the introduction of the post partum blues syndrome by 15 participants (75%) in the good category, 5 participants (25%) in the sufficient category.